2021
DOI: 10.3892/ijmm.2021.4923
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine suppresses the development of abdominal aortic aneurysm by downregulating the mircoRNA‑21/PDCD 4 axis

Abstract: Abdominal aortic aneurysm (AAA) is a pathological state with permanent dilation, which indicates a fatal potential for aortic rupture. It has been reported that dexmedetomidine (dex) and microRNA (miR)-21 are involved in the progression of AAA. Thus, the present study aimed to investigate the joint effects of these factors on AAA treatment. For this purpose, rat models of AAA were established with enzyme perfusion and the rats were then injected with dex. Alterations in the abdominal aorta in rats with AAA wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 49 publications
0
7
0
2
Order By: Relevance
“…Successful induction was defined as the appearance of hemiplegia 24 h after MCAO. Rats were euthanized by an injection of excessive sodium pentobarbital (800 mg/kg) ( 40 ); successful euthanasia was defined as the disappearance of reflex and respiration, and cardiac arrest. Following euthanasia, the brain tissues of 6 rats from each group were randomly selected for triphenyltetrazolium chloride (TTC) staining, and those from the other 10 rats were collected for follow-up biochemical tests.…”
Section: Methodsmentioning
confidence: 99%
“…Successful induction was defined as the appearance of hemiplegia 24 h after MCAO. Rats were euthanized by an injection of excessive sodium pentobarbital (800 mg/kg) ( 40 ); successful euthanasia was defined as the disappearance of reflex and respiration, and cardiac arrest. Following euthanasia, the brain tissues of 6 rats from each group were randomly selected for triphenyltetrazolium chloride (TTC) staining, and those from the other 10 rats were collected for follow-up biochemical tests.…”
Section: Methodsmentioning
confidence: 99%
“…25 The proliferative effect of TGF-β1 on ASMCs was first ascertained in this study as demonstrated by increased cell viability and proliferation of ASMCs after TGF-β1 treatment, and TGF-β1-repressed cell apoptosis of ASMCs. Dexmedetomidine has been reported to enhance expression of miR-21 and reduce expression of programmed cell death protein 4 to repress the development of abdominal aortic aneurysm, 26 and TGF-β1 up-regulated miR-181a to decrease phosphatase and tensin homologue deleted on chromosome ten (PTEN) in asthmatic mice. 27 Therefore, dexmedetomidine might regulate miR-181a/PTEN to be implicated in the TGF-β1-induced ECM production and proliferation of ASMCs.…”
Section: Discussionmentioning
confidence: 99%
“…All SD rats were randomly divided into sham and AAA groups, with 6 animals in each group. AAA animal models were constructed as described previously [ 19 , 20 ]. In brief, SD rats in the AAA group were anesthetized with 2.5% gaseous isoflurane and subjected to systemic heparinization.…”
Section: Methodsmentioning
confidence: 99%